Simultaneous Measurement of Temperature and Strain Using Two Fiber Bragg Gratings Embedded in a Glass Tube - Song, M.; Lee, S.B.; Choi, S.S.; Lee, B. (Academic Press Inc., 1997)
A simple and effective technique for the simultaneous measurement of temperature and strain using two closely spaced fiber gratings embedded in series in a silica glass capillary tube is described. One of the two gratings is firmly attached to a carefully designed glass tube and thus responds to heat only, while the other one responds to both heat and strain. ？ 1997 Academic Press.